2023
DOI: 10.1002/iid3.960
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between human papillomavirus and oral lichen planus: A systematic review of the literature

Abstract: IntroductionOral lichen planus (OLP) is a chronic inflammatory disorder with cell‐induced immunopathological responses and is considered a potential malignancy disorder in the oral cavity. Due to the high prevalence of OLP as well as the potential for malignancy, human papillomaviruses (HPVs) may play an important role in it. Although previous studies have explored the possible relationship between HPV and OLP, the findings have been conflicting and nonconclusive. This study aims to review the studies that inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…For the same reasons, the anatomic location of the oral lesions and clinical subtype of the OLP were not analyzed in correlation with the HPV status. This remains accordant with the observations of Agha-Hosseini and Hafezi Motlagh, who also concluded that the prevalence of HPV in OLP has not been widely discussed in terms of the clinical type of OLP lesions, and further investigation of this topic is definitely required [9]. The methods for the sample collection and the HPV detection used in the included studies were not uniform, which partially results from the wide timeframe of the described research, ranging from 1987 to 2023.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…For the same reasons, the anatomic location of the oral lesions and clinical subtype of the OLP were not analyzed in correlation with the HPV status. This remains accordant with the observations of Agha-Hosseini and Hafezi Motlagh, who also concluded that the prevalence of HPV in OLP has not been widely discussed in terms of the clinical type of OLP lesions, and further investigation of this topic is definitely required [9]. The methods for the sample collection and the HPV detection used in the included studies were not uniform, which partially results from the wide timeframe of the described research, ranging from 1987 to 2023.…”
Section: Discussionsupporting
confidence: 71%
“…In our search, we did not find any results of the research on the prevalence of HPV in OLP before and after corticosteroid therapy. This issue was also pointed in a Agha-Hosseini and Hafezi Motlagh review, who emphasized the necessity to extend studies in this field [9].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations